Effects of Organic Acid Coagulants on the Textural and Physical–Chemical Properties of Tofu - Carolina Paz-Yépez; Mariana Gavilanes-Tomalá; Julio Palmay-Paredes; Grace Medina-Galarza; Sebastián Guerrero-Luzuriaga; Borja Velázquez Martí (Applied Sciences)
Tofu is obtained by heating soymilk, to which a coagulant, such as calcium sulfate or magnesium chloride, is added to make it curdle. This study aimed to parameterize the effects of the following three alternative organic coagulant types: apple, rice, and white vinegars, used in different proportions. Six treatments were established with three concentrations (1%, 3%, and 5%), evaluating the coagulation time and curd yield. The treatments with the lowest coagulation time were analyzed for texture by TPA, color through the CIEL*a*b scale, protein content, and moisture. The results showed that the rice vinegar + 3% white vinegar (T6C3) treatment showed the lowest coagulation time (0.78 min). The 5% apple vinegar (T1C5) treatment provided the highest curd yield, averaging 23.73%. This treatment’s protein and moisture contents were 3.93% protein and 69.73% moisture, confirming that better texture characteristics are recorded in tofu at lower pH values. The TPA results showed that using apple and rice vinegars as coagulants provided a challenging, less cohesive, more adhesive, and less elastic tofu. White vinegar provided a soft, more cohesive, less adhesive, and more elastic tofu. In the color analysis, it was observed that tofu coagulated with apple vinegar showed a tendency toward a yellow color, and tofu coagulated with rice and white vinegars showed a tendency toward a white color. These findings parameterize the effects of using each type of vinegar as a coagulant. These organic coagulants provide faster coagulation times and desirable texture characteristics, thus offering a practical alternative to traditional coagulants in tofu manufacturing.